2020
DOI: 10.1093/aob/mcaa160
|View full text |Cite
|
Sign up to set email alerts
|

Fundamentally different repetitive element composition of sex chromosomes in Rumex acetosa

Abstract: Background and Aims Dioecious species with well-established sex chromosomes are rare in the plant kingdom. Most sex chromosomes increase in size but no comprehensive analysis of the kind of sequences which drive this expansion has been presented. Here, we analyse sex chromosome structure in common sorrel (Rumex acetosa), a dioecious plant with XY1Y2 sex determination, and we provide the first chromosome specific repeatome analysis for a plant species possessing sex chromosomes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 107 publications
1
16
0
Order By: Relevance
“…In diploid organisms, only the Y chromosomes are predicted to degenerate, because X chromosomes recombine in the XX females (reviewed in Charlesworth, 2015 ). However, X‐ as well as Y‐linked regions are expected to accumulate repetitive sequences to a greater extent than nonsex‐linked genome regions, due to their somewhat lower effective population size, and this has been detected in papaya and common sorrel (Jesionek et al, 2020 ; Wang, Na, et al, 2012 ). The S. dunnii X‐LR appears to have done the same, being rich in LTR‐Gypsy elements (Table 3 ; Figures 1a and 3a ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In diploid organisms, only the Y chromosomes are predicted to degenerate, because X chromosomes recombine in the XX females (reviewed in Charlesworth, 2015 ). However, X‐ as well as Y‐linked regions are expected to accumulate repetitive sequences to a greater extent than nonsex‐linked genome regions, due to their somewhat lower effective population size, and this has been detected in papaya and common sorrel (Jesionek et al, 2020 ; Wang, Na, et al, 2012 ). The S. dunnii X‐LR appears to have done the same, being rich in LTR‐Gypsy elements (Table 3 ; Figures 1a and 3a ).…”
Section: Discussionmentioning
confidence: 99%
“…The expected accumulation has been detected in both Y‐ and W‐linked regions of several plants with heteromorphic sex chromosome pairs (reviewed by Hobza et al, 2015 ). Repeat accumulation is also expected in X‐ and Z‐linked regions; although this is expected to occur to a much smaller extent, it has been detected in Carica papaya and Rumex acetosa (Gschwend et al, 2012 ; Jesionek et al, 2020 ; Wang, Na, et al, 2012 ). The accumulation of repeats reduces gene densities, compared with autosomal or pseudoautosomal regions (PARs), and this has been observed in Silene latifolia , again affecting both sex chromosomes (Blavet et al, 2015 ).…”
Section: Introductionmentioning
confidence: 96%
“…Although, plant sex chromosomes are not without consequences from suppressed recombination. A consistent pattern found is an enrichment of transposable elements (TEs) and other repeats [65,[76][77][78], which often accumulate in regions of low recombination [79]. In fact, in several species TE expansions have instead driven the Y chromosome to be larger than the X, such as in Coccinia grandis [80] and S. latifolia [81].…”
Section: "The Discovery Referred To In a Preceding Footnote That The Spermatogonial Number Of Anasa Is 21 Instead Of 22 Again Goes Far Tomentioning
confidence: 93%
“…In many species, dioecy has evolved recently, so these plants provide an excellent model for studying the early stages of sex chromosome divergence, which later in evolution leads to gradual sex chromosome degeneration (Hobza et al 2018). Z. Kubát (IBP) showed that some TEs proliferate preferentially either in the male or in the female germline which can be connected with specific circumstances affecting TE management and activity in male and female plants and during gametophyte formation (Jesionek et al 2021). The process of evolutionary diversification of sex chromosomes is also connected with specific chromatin modifications of both histones and cytosines in Silene latifolia as demonstrated by M. Hubinský (IBP) (Rodríguez Lorenzo et al 2020).…”
Section: Unravelling the Mysteries Of Plant Sex-and B-chromosomesmentioning
confidence: 99%